21st Century Skills and the English Foreign Language Classroom: A Call for More Awareness in Colombia (GIST – Education and Learning Research Journal, 2013)
The 21st century demands the explicit integration of learning strategies, digital competences and career abilities. Schools in general and EFL classrooms in particular should provide students with practices and processes focused on acquiring and developing, among other things, creativity, critical thinking, collaboration, self-direction, and cross-cultural skills. In this regard, the Partnership for 21st Century Skills (2007) argues for the explicit integration of learning and innovation skills, information, media and digital literacy skills, and life and career skills. Despite its relevance, a basic review of Colombian scholarly publications suggests that little has been done in order to infuse the EFL class with some of these ideas. Consequently, this paper seeks to inform and motivate Colombian EFL teachers to incorporate meaningful and intellectually stimulating alternatives that allow students not just to learn English, but more importantly to understand complex perspectives, use multiple media and technologies, and work creatively with others.
Keywords: 21st century skills; new literacies; technology; English language teaching; English as a foreign language.